2000
DOI: 10.1093/bja/85.6.869
|View full text |Cite
|
Sign up to set email alerts
|

Central cholinergic depletion induced by 192 IgG-Saporin alleviates the sedative effects of propofol in rats

Abstract: We examined the effect of central cholinergic depletion on the sedative potency of propofol in rats. Depletion was produced by intracerebroventricular administration of an immunotoxin specific to cholinergic neurones (192 IgG-Saporin; 2 microg). As a result of this lesion, acetylcholine concentration was reduced by about 40% in the frontoparietal cortex and in the hippocampus but was essentially normal in the striatum and cerebellum. Sedation in rats was assessed as the decrease in locomotor activity. Sedative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 25 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…An anticholinesterase that increased central Ach levels was shown to reduce the depth of anesthesia induced by propofol or isoflurane (Meuret et al, 2000;Hudetz et al, 2003). Pain et al (2000) reported that central Ach depletion by intracerebroventricular (icv) administration of 192IgG-saporin reduced the sedative potency of low-dose (30 mg/kg i.p.) propofol, although a subsequent study (Laalou et al, 2008) reported that the same depletion increased the anesthesia potency of propofol (N100 mg/kg i.p.).…”
Section: Introductionmentioning
confidence: 99%
“…An anticholinesterase that increased central Ach levels was shown to reduce the depth of anesthesia induced by propofol or isoflurane (Meuret et al, 2000;Hudetz et al, 2003). Pain et al (2000) reported that central Ach depletion by intracerebroventricular (icv) administration of 192IgG-saporin reduced the sedative potency of low-dose (30 mg/kg i.p.) propofol, although a subsequent study (Laalou et al, 2008) reported that the same depletion increased the anesthesia potency of propofol (N100 mg/kg i.p.).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the immunotoxin 192 IgG-Saporin selectively destroys basal forebrain cholinergic neurons. In rat, intracerebroventricular administration of 192 IgG-Saporin caused a reduction in ACh levels in frontoparietal cortex and hippocampus and a decrease in propofol-induced locomotor inhibition 16 . These findings suggest that inhibition of basal forebrain cholinergic neurons contributes to the hypnotic effect of propofol 16 .…”
Section: 4mentioning
confidence: 94%
“…62 The small dose of adenosine A 1 agonist injected into the pontine reticular formation caused a surprisingly long duration antinociceptive effect. 377 In humans, systemic administration of sedative hypnotics that enhance the actions of GABA increase NREM sleep and decrease REM sleep. 359 Adenosine A 1 receptors are coupled to G proteins, which amplify synaptic signaling in the time domain.…”
Section: Arousal States Are Regulated By Multiple Neurotransmitters Amentioning
confidence: 99%